Airlife's helicopters and rotorcraft - Simpson, R. W. (Airlife, 1998)
This companion volume to "Airlife's General Aviation" provides a comprehensive reference to all helicopter types and models built since 1945. A short history of the product development of each manufacturer is given, followed by descriptions of each type, both military and civil.